1989
DOI: 10.1111/j.1439-0442.1989.tb00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Degradation and Outflow of Amino Acids in Cows

Abstract: Summary Two rumen‐ and duodenum‐cannulated cows were used to study the disappearance rate, degradation in, and outflow from the rumen of four amino acids administered individually into the rumen at the following dose levels (mmol): lysine 273–547‐820, tyrosine 276–496‐828, isoleucine 381–762‐1143, methionine 335. Calculations were based on the use of PEG (polyethylene glycol, 4000) as liquid marker for determination of the volume and dilution rate of rumen fluid. At the same dry matter intake a comparison was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…In agreement with this Kowalczyk (1994) concluded, after comparing in vitro and in vivo ruminal deg radation of free amino acids, that amino acids disappeared faster in vivo than in vitro, and that only small proportions of free amino acids appeared at the duode num. Other experiments has though indicated that a dose dependent ruminal es cape of free amino acids takes place (Cottle and Velle, 1989;Sulu et al, 1989;Velle et al, 1997), and is enhanced by the dosage of free amino acids in mixtures and that the apparent degradation rate of free amino acids is not dependent on feed level (Volden et al, 1998). There is thus substantial reason to believe that amino acid composition of undegraded feed protein flowing to the duodenum, is different compared to the original feed.…”
Section: Degradation In the Rumen Of Amino Acids In Feed Proteinmentioning
confidence: 99%
“…In agreement with this Kowalczyk (1994) concluded, after comparing in vitro and in vivo ruminal deg radation of free amino acids, that amino acids disappeared faster in vivo than in vitro, and that only small proportions of free amino acids appeared at the duode num. Other experiments has though indicated that a dose dependent ruminal es cape of free amino acids takes place (Cottle and Velle, 1989;Sulu et al, 1989;Velle et al, 1997), and is enhanced by the dosage of free amino acids in mixtures and that the apparent degradation rate of free amino acids is not dependent on feed level (Volden et al, 1998). There is thus substantial reason to believe that amino acid composition of undegraded feed protein flowing to the duodenum, is different compared to the original feed.…”
Section: Degradation In the Rumen Of Amino Acids In Feed Proteinmentioning
confidence: 99%
“…Total ruminal outflow of free Lys did not differ when it was supplied with or without Met (P = 0.08) and reached, respectively, 26.6 ± 5.5 and 27.5 ± 5.5 g. In this study, high ruminal escape of Met and Lys were observed despite dietary conditions favourable to AA degradation. High concentrate diets actually induce an efficient growth of microorganisms [16] and a selection of amylolytic bacteria that utilise high proportions of AA [24]. However, more than 65% of the total amounts of free Met and free Lys that escaped ruminal fermentation did so during the first 4 h. According to Velle et al [23], ruminal escape of free AA is increased when they are administered with larger amounts of other AA.…”
Section: Resultsmentioning
confidence: 99%
“…The ruminal escape of free AA has been shown to vary with AA [22], dietary conditions [16], amount supplied [24], and whether the AA is administered individually or with other AA [23]. To our knowledge, only Campbell et al [2] has investigated free AA supplementation for growing cattle, and observed no effect on animal performances although the amounts supplied were modest.…”
mentioning
confidence: 97%
“…Supplementing AA in low-quality forage-based diets promotes protein accretion and N retention (Volden et al 2001). Sulu et al (1989) fed cattle two different diets supplemented with AA and observed that the degradation rates of these AAs in the forage-based diet were less and escaped more from the rumen as compared with the high concentrate diets.…”
Section: Presence Of Other Aasmentioning
confidence: 99%